Bibliometric analysis of human monkeypox research from 1975 to 2022 and novel prevention and control strategies - Lin, Jiyong; Li, Guiyu; Zhong, Peiling; Zeng, Qiang; Liu, Lei; Chen, Liang (Frontiers in Public Health, 2022)
Background Since human monkeypox was reported, many related literatures have been published. This study aimed to evaluate the research hotspots and future development trends of human monkeypox by a bibliometric analysis, to analyze the preventive and control measures of various countries in response to human monkeypox outbreaks. Methods The Web of Science Core Collection database was searched for all monkeypox related literature published from 1975 to 2022, and the search strategy was “TS = monkeypox.” Bibliometric analysis was performed using VOSviewer software based on retrieval data. Contribution metric methods and visualization were used to analyze the top issues in the field of human monkeypox. Results From 1975 to 2022, a total of 1,068 monkeypox research papers were included, of which American researchers published 663 papers, and it was also the country that participated in the most international cooperation. Centers for Disease Control Prevention USA is the most prolific institution and a leader in research collaborations. The Journal of Virology has the largest number of published papers on monkeypox. In addition, Damon Inger K has made significant contributions to monkeypox research, with both the most published and the most citation. A total of 2,847 keywords were identified, four top topics were obtained through cluster analysis: (1) human monkeypox epidemiology and species research. (2) human monkeypox virus vaccine and experimental research. (3) human monkeypox disease diagnosis and treatment studies. (4) human monkeypox disease prevention and immunization studies. To curb the spread, regions or countries have developed and implemented detailed managements. The prevention and control measures focus on the isolation of suspected or confirmed patients, the investigation and tracking of the source of the disease, the disposal of pollutants, vaccination and the protection of health workers. Conclusions The number of human monkeypox literature has grown since 2003. Infection, vaccine and efficacy were the top topic over the past 47 years while the contact tracing, testing, surveillance and vaccination have been the major concerns since the human monkeypox outbreak in May 2022. The treatment and management of human monkeypox deserves further attention.